RELASI KUASA DALAM KEPEMIMPINAN ADAT : Studi Relasi Kuasa dalam Model Kepemimpinan Adat di Kampung Kuta, Ciamis, Jawa Barat - Subhan Agung (Jurnal Ilmu Politik dan Pemerintahan, 2011)
This paper is the theme of power relation in the model of Traditional Leadership in the village of Kuta, Ciamis West Java.  This article tries to reveal how indegious leaders in the village of Kuta problems does play a political role in their leadership rolesrespectively.  It is realize or not, each leader tried to strengthen his control over the roles and communication esthablisd between them.  In addition, how these leaders scramble influence in the eyes of the people with legitimate power through what they call amandate ancestor. By using ethnographic qualitative research methods, the authorstied to describe as well as exploring the issues listed above. This is important because basically all the processes taking placein communications and community leaders is the knowledge that will be able answer the problems which appear above. Amanah ansector which they use as jargon to keep the power of a leader is basically something that is planned (by design) in the context of power relations that shaped their respective leaders.